The Impact of Heat Treatment on the Domain Configuration and Strain Behavior in Pb[Zr, Ti]O3 Ferroelectrics. Issue 1 (1st October 2014) - Schmitt, Ljubomira Ana; Kungl, Hans; Hinterstein, Manuel; Riekehr, Lars; Kleebe, Hans‐Joachim; Hoffmann, Michael J.; Eichel, Rüdiger‐A.; Fuess, Hartmut; Johnson, D.
<x xml:space="preserve">Abstract</x> The influence of heat treatment in lead zirconate titanate Pb(Zr, Ti)O3 (PZT) ferroelectrics on the domain structure and strain behavior has been investigated. Temperature‐induced changes in the domain configuration, for example, appearance of nanodomains within microdomains, were observed by in situ hot‐stage transmission electron microscopy. During the transient post annealing state the strain behavior under electric field differed from that of the nonheat‐treated ferroelectrics. Directly after cooling the difference was most pronounced and decreased as a function of time. The enhanced response to an electric field of 4 kV/mm resulted in qualitatively different effects on strain for PZT from the tetragonal side and from the rhombohedral side of the morphotropic phase boundary.